WORKSHOP PENDAMPINGAN PERAKITAN DAN INSTALASI KOMPUTER BAGI SISWA KELAS X MULTIMEDIA - Mustofa, M Iqbal; Sari, Nindy Devita; Vaujiah, Nadif; Sari, Anti Nurlaila (Universitas Mataram, 2024)
The implementation of this service is motivated by the lack of understanding and skills of the tenth-grade Multimedia students at Nurul Huda Vocational High School in basic computer knowledge, even though this serves as the foundation of knowledge that students must possess when they enter the Computer Information Technology (CIT) program. Therefore, this service aims to enhance students' abilities in basic technology corresponding to their field of expertise. The implementation method of this service involves four stages, beginning with observation, followed by group discussions, mentoring, and evaluation. The service was conducted on November 23, 2023, with 39 participants from classes A and B of the Multimedia competency. Mentoring commenced with the delivery of fundamental software and hardware computer materials to enhance students' knowledge competencies, followed by computer assembly mentoring from basics to operational units. This ensures that students are not only proficient in theoretical knowledge but also capable of applying the knowledge they have acquired. The service concluded with an evaluation stage, which involved pre-test and post-test questions totaling 20 questions given to the students. From the evaluation results, it was concluded that computer assembly mentoring has increased students' abilities by 25%.